2013
DOI: 10.4137/ccrep.s10534
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ Thyrotoxicosis-Induced Reversible Cardiomyopathy: A Case Report

Abstract: The objective of this report is to present a case of Graves’ thyrotoxicosis-induced cardiomyopathy. This is a case of a 26 year old woman that presented with severe symptomatic congestive heart failure and was subsequently diagnosed with dilated cardiomyopathy secondary to Graves’ disease. Despite an initial left ventricular systolic ejection fraction of 20% on echocardiography, treatment with anti-thyroid agents led to rapid improvement of her clinical status and normalization of her ejection fraction. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Definitive treatment with radioactive iodine ablation or thyroidectomy may also be considered to rapidly recover cardiac function [1]. Several studies have validated a reversal of echocardiographic abnormalities in these patients, once a euthyroid state has been established [1,46,47]. Additional treatment may include beta-adrenergic blockade to reduce heart rate, and diuretics to improve congestive symptoms [1].…”
Section: Discussionmentioning
confidence: 99%
“…Definitive treatment with radioactive iodine ablation or thyroidectomy may also be considered to rapidly recover cardiac function [1]. Several studies have validated a reversal of echocardiographic abnormalities in these patients, once a euthyroid state has been established [1,46,47]. Additional treatment may include beta-adrenergic blockade to reduce heart rate, and diuretics to improve congestive symptoms [1].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] The possible relationship between dilated cardiomyopathy, Takotsubo cardiomyopathy, and Graves' disease is reported in the literature. 11,12 Hübner et al experimentally revealed impairment of cardiac performance in both adolescent and adult mice with Graves' disease. The cardiac performance could be partly restored by early hormonal treatment, but adult mice lacked this recovery potential.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the other complications of GD, cardiomyopathy is life-threatening and therefore most of the patients who recover from cardiomyopathy are advised to undergo radioactive iodine ablation or thyroidectomy 3 4 5 6) . However, our patient did not undergo thyroidectomy or radioactive iodine ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Although GD has been reported to cause DCMP in adults, the mechanism has not been documented precisely. There have been several reports of adults with DCMP due to GD, as well as of infants with congestive heart failure secondary to transient neonatal thyrotoxicosis 3 4 5 6) . Most of these patients are reported to have recovered completely after a euthyroid state was established, although a few of the adult patients died 5) .…”
Section: Introductionmentioning
confidence: 99%